Step-Ladder Expansive Cranioplasty: A Study on a Cadaveric Model - Sengupta, Sudip Kumar; Tandon, Sanjeev; Sahi, Indra Bahadur (Indian Journal of Neurosurgery, 2018)
Notwithstanding the ongoing debates on the necessity, indication, extent, and technique of achieving decompressive hemicraniectomy (DC), any procedure that can deliver the envisaged advantages of a DC, without having to take up the patient for a second surgery in the form of cranioplasty, can be of a great advantage in situations in which DC is being used.Step-ladder expansive cranioplasty has been proposed as an effective single-step alternative to DC and cranioplasty at a later date, resulting in a fixed but assured volume augmentation. Recently, a case report has emerged documenting a successfully managed case of acute subdural hematoma (SDH) using this technique. In the present in vitro study, an attempt has been made to evaluate different variants of step-ladder expansive cranioplasty constructs using cadaver and clay models.The findings suggest that the cranial volume expansion in step-ladder expansive cranioplasty is not dependent solely on the patient's skull bone thickness. If the clinical trials prove the procedure to be safe, it can be used at one end, as an alternative to preserving the bone flap at another site prior to cranioplasty, and as a complete one-stage alternative to DC and cranioplasty at a later date, on the other.
Keywords: decompressive hemicraniectomy; step-ladder expansive cranioplasty; cadaveric model